Fiqih dalam Perspektif Filsafat Ilmu: Hakikat dan Objek Ilmu Fiqih - Shaifudin, Arif (Fakultas Syariah INSURI Ponorogo, 2019)
Every Muslim is aware and at the same time believes that all the activities of his life in his capacity as a creature of Allah certainly will not be separated from the signs of shari'ah. There are norms that regulate and bind every activity carried out along with the legal consequences. This rule or norm is commonly referred to as jurisprudence. Fiqh with this meaning is the fiqh that we find in religious practices or Muslim activities every day. But there is one anxiety when jurisprudence is read with academic glasses that require scientific empiricism. This is important to answer in order to provide proof of